Strategi Komunikasi Politik Tim Sukses Pemenangan Pemilu Anies-Amin dalam Membangun Dukungan Publik melalui Twitter - Mukharomah, Nurul; Lenggana, Wulan Furrie (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Anies Baswedan and Muhaimin Iskandar are two political figures with different backgrounds and profiles, but both have significant achievements. They face rivalry in the 2024 election with other candidates from political parties or independents. Their winning teams played an important role in shaping the candidate's image and gaining public support, especially through social media. This research focuses on the political communication strategy of the AMIN success team in gaining public support via Twitter. The research method used is qualitative with in-depth interviews and observation. The research results show that the team successfully used four communication strategies: propaganda and persuasion, use of mass media, agenda setting and framing, and public participation and interaction. The successful team faced several obstacles, including segments of society that were not active on social media and limited campaign funds. This hinders the implementation of broader and more inclusive communication strategies, such as face-to-face campaigns and the use of traditional media. Even though the strategy on Twitter has succeeded in creating an interactive digital public space, it is still necessary to expand the reach of the campaign and overcome funding limitations to increase the overall effectiveness of the campaign.